Modulation of nitric oxide bioavailability attenuates ischemia-reperfusion injury in type II diabetes - Gazyakan, Emre; Hirche, Christoph; Reichenberger, Matthias; Urbach, Olena; Germann, Günter; Engel, Holger (Journal of plastic, reconstructive & aesthetic surgery, 2021)
Background - Diabetes mellitus increases the susceptibility of free tissue transplantations to ischemia-reperfusion injury. The aim of this study was to enhance nitric oxide (NO) bioavailability through exogenous NO synthase and the substrate L-arginine to attenuate ischemia reperfusion-induced alterations in a type 2 diabetes rodent model. - Material and Methods - Sixty-four Wistar rats were divided into 8 experimental groups. Type 2 diabetes was established over 3 months with a combination of a high-fat diet and streptozotocin. A vascular pedicle isolated rat skin flap model that underwent 3 h of ischemia was used. At 30 min before ischemia, normal saline, endothelial NOSs (eNOSs), inducible NOSs, neuronal NOSs (1 and 2 IU), and L-arginine (50 mg/kg body weight) were administered by intravenous infusion alone or in combination. Ischemia-reperfusion-induced alterations were measured 5 days after the operation. - Results - The three isoforms of NOS significantly increased the flap vitality rate (VR) between 20% and 28% as compared to the control group (3%). Sole L-arginine administration increased the VR to 33%. The combination of L-arginine with NOS resulted in a further increase in flap VRs (39%-50%). Best results were achieved with the combination of eNOS and L-arginine (50%). An increase in enzyme dosage led to decreased VRs in all NOS isoforms alone and even in combination with L-arginine. - Conclusion - Modulation of NO bioavailability through the exogenous application of NOSs and L-arginine significantly attenuated ischemia-reperfusion-induced alterations in a type 2 diabetic skin flap rat model. The combination of enzyme and substrate result in the highest VRs. Higher enzyme dosage seems to be less effective. This pharmacological preconditioning could be an easy and effective interventional strategy to support the conversion of L-arginine to NO in ischemic and in type 2 diabetic conditions.